2011
DOI: 10.4269/ajtmh.2011.10-0449
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Cryptosporidium hominis from Water Samples in São Paulo, Brazil

Abstract: The protozoan parasite Cryptosporidium has emerged as one of the most important water contaminants, causing waterborne outbreaks of diarrheal diseases worldwide. The small size of oocysts under the microscope and the possibility of changes in characteristics of oocysts, mainly in environmental samples, make the taxonomy of the genus difficult if morphologic characteristics are considered. This limitation encouraged the application of molecular methods to identify this microorganism. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…In China, Xiao et al (2013) found oocysts of this parasite in 86.4% of water catchment areas and Lee et al (2014) reported its prevalence in 23.1% of Malaysian rivers. In Brazil, Araújo et al (2011) described the occurrence of this parasite in 30% of the water samples collected in state of São Paulo, whereas Osaki et al (2013) found Cryptosporidium spp. in 2/4 of the water catchment systems in Curitiba, Paraná State.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, Xiao et al (2013) found oocysts of this parasite in 86.4% of water catchment areas and Lee et al (2014) reported its prevalence in 23.1% of Malaysian rivers. In Brazil, Araújo et al (2011) described the occurrence of this parasite in 30% of the water samples collected in state of São Paulo, whereas Osaki et al (2013) found Cryptosporidium spp. in 2/4 of the water catchment systems in Curitiba, Paraná State.…”
Section: Discussionmentioning
confidence: 99%
“…have been conducted with the goal of better understanding the environmental epidemiology of this parasite. Many studies describe the occurrence of C. meleagridis, C. hominis, C. parvum and C. andersoni in water samples (ARAÚJO et al, 2011;LEE et al, 2013;RUECKER et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium is an enteric protozoan parasite whose oocysts are often transmitted via water, with several species of Cryptosporidium spp. being identified in the water (reservoirs) in Brazil [ 16 , 17 ], and also in the water of swimming pools [ 18 , 19 , 20 ]. The parasite lifecycle and pathophysiology have been well described [ 21 ], and it has been found in over 150 vertebrate hosts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Giardia spp. cysts were detected in many Brazilian environmental samples: wastewater, water (superficial and recreational), and bivalve mollusks [ 6 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%